Changes in physico-chemical properties during fruit development of Japanese pumpkin (Cucurbita maxima) - N. Muenmanee (2018)
© All Rights Reserved. Changes in physico-chemical properties such as specific gravity (SG), color development, fruit firmness, moisture content (MC), dry matter (DM), total carotenoids, total chlorophyll, crude fiber, starch content, sugar content and total soluble solids in Japanese pumpkin fruit 'Cucurbita maxima' were investigated during fruit development. The results revealed that the fruits gradually accumulated dry matter, total soluble solids, total sugars, total carotenoids, total chlorophylls, starch content and crude fiber along fruit development. The values of the aforementioned parameters were 6.93-16.00%, 4.5-12.0%, 16.0-23.55 mg/g, 1.86-2.83 mg/100g, 12.56-49.42 mg/100g and 1.56-2.54%, respectively. Based on the changes of these parameters during fruit development, harvesting at 50 days after fruit set was considerably recommended due to the fruits had optimum maturity and the quality also agreed with market and consumer acceptability.